2010
DOI: 10.1111/j.1651-2227.2009.01644.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of urine dipstick testing in children with suspected UTI: a systematic review of relationship with age and comparison with microscopy

Abstract: Urine dipstick testing is more effective for diagnosis of UTI in children over 2 years than for younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 15 publications
2
50
1
7
Order By: Relevance
“…When strict criteria were applied for patient enrollment and urine collection, the diagnostic performance of conventional rapid urine tests in our study was remarkable compared to that previously reported [14,19]. Nevertheless, the finding that a number of children were misclassified and unnecessary treated with antibiotic therapy due to false positive rapid urine tests emphasized the need for a rapid assay with better accuracy.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…When strict criteria were applied for patient enrollment and urine collection, the diagnostic performance of conventional rapid urine tests in our study was remarkable compared to that previously reported [14,19]. Nevertheless, the finding that a number of children were misclassified and unnecessary treated with antibiotic therapy due to false positive rapid urine tests emphasized the need for a rapid assay with better accuracy.…”
Section: Discussioncontrasting
confidence: 63%
“…A recent study showed that urine HBP (UHBP) provided better sensitivity and specificity compared to urine dipstick analysis in children with upper or lower urinary tract infection (UTI) [8]. As some reports demonstrated that urine microscopy had better accuracy than dipstick analysis in young children [14,12], the diagnostic performance of UHBP in comparison to urine microscopy is of paramount interest and has yet to be determined.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…If however the patient with symptoms of UTI is not severely sick, a urine sample can be obtained by the most convenient method (for example adhesive urine bag) and sent for urinalysis and microscopy. If this urine sample is negative for leukocyte and nitrites, the likelihood of UTI is low (Mori et al 2010;Ramlakhan et al 2011); if however leucocytes and/nitrites are detected, a second urine sample should be obtained by a bladder catheter or SPA and sent for urine culture.…”
Section: Diagnosismentioning
confidence: 99%
“…12 Dipstick has been shown to perform well in children $2 years old as a screening test for UTI. 13 Microscopic examination of urine requires technicians with special training in laboratories using CLIA-certified methods. 12 Previous studies have questioned the additional benefit of microscopy over dipstick urinalysis in children; however, these studies included few infants 1 to 90 days of age.…”
mentioning
confidence: 99%